Ambiente hospitalar: um estudo das práticas lúdicas educativas no Hospital Universitário Lauro Wanderley - Clark, Anne Jaqueline (2023)
During the hospitalization process, the child stays away from his daily life, from his family, school, friends, from the reality of life in society, such facts directly and indirectly influence his emotional system and the recovery process. Suspension of day-to-day activities can hinder the child's biopsychosocial development, which can then cause damage to the quality of life, the learning development process, and the recovery process. This work seeks to demonstrate the need for alternative informal learning spaces with playful activities, mediated by the pedagogue in the health units and the optimizing results of the pedagogical actions, as they positively influence the recovery of these children interned in health units, guaranteeing school bonds. The ludicity of the activities in these alternative education spaces becomes an “educational attraction” in the teaching and learning process, stimulating the intellectual development and recovery ofthis student. The child better expresses his feelings, his desires and better absorbs the new moment he is going through when he has in the routine the reception of ludic educational practices. The study is divided into two stages of theoretical and methodological construction: firstly, a bibliographical and documentary survey was carried out, and in the second moment, a field research was carried out with the application of a questionnaire virtually due to the pandemic hospital context and the challenges of COVID 19. six people participated in the research, distributed among health professionals who work in pediatrics at the HULW and education professionals who are members of the project: “Psychopedagogical care for hospitalized children and adolescents: alternative work for the pedagogue”. Teaching and learning in the hospital environment is a great challenge, which is overcome every day.